Growth, tolerance and safety outcomes with use of an extensively hydrolyzed casein-based formula in infants with cow’s milk protein allergy - Kansu, Aydan; Urganci, Nafiye; Bukulmez, Aysegul; Kutluk, Gunsel; Gulcu Taskin, Didem; Sahin Keskin, Lutfiye; Igde, Mahir; Molon, Lutfi; Dogan, Yasar; Sekerel, Bulent Enis; Yuksek, Mutlu; Bostanci, Ilknur; et al. (Frontiers in Pediatrics, 2023)
Objective: To evaluate growth, tolerance and safety outcomes with use of an extensively hydrolyzed casein-based formula (eHCF) in infants with cow's milk protein allergy (CMPA). Methods: A total of 226 infants (mean±SD age: 106.5±39.5 days, 52.7% were girls) with CMPA who received eHCF comprising at least half of the daily dietary intake were included. Data on anthropometrics (weight for age [WFA], length for age [LFA] and weight for length [WFL] z-scores) were recorded at baseline (visit 1), while data on infant feeding and stool records, anthropometrics and Infant Feeding and Stool Patterns and Formula Satisfaction Questionnaires were recorded at visit 2 (on Days 15±5) and visit 3 (on Days 30±5). Results: From baseline to visit 2 and visit 3, WFA z-scores (from -0.60±1.13 to -0.54±1.09 at visit 2, and to -0.44±1.05 at visit 3, p<0.001) and WFL z-scores (from -0.80±1.30 to -0.71±1.22 at visit 2, and to -0.64±1.13 at visit 3, p=0.002) were significantly increased. At least half of infants never experienced irritability or feeding refusal (55.7%) and spit-up after feeding (50.2%). The majority of mothers were satisfied with the study formula (93.2%), and wished to continue using it (92.2%). Conclusions: In conclusion, eHCF was well-accepted and tolerated by an intended use population of infants ≤ 6 months of age with CMPA and enabled adequate volume consumption and improved growth indices within 30 days of utilization alongside a favorable gastrointestinal tolerance and a high level of parental satisfaction.